PENGGUNAAN RETURN ON INVESTMENT DAN RESIDUAL INCOME GUNA MENILAI KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013) - Dhea Indira Ard (Jurnal Administrasi Bisnis, 2015)
Abstract The company needs to improve its financial performance to achieve maximum profit by implementing the strategy in the management of the company, as well as evaluating the financial performance of companies with financial analysis. Pharmaceutical firms is a research-based company that simultaneously require a Research and Development and promotion spend not less, and its products are strictly regulated, both at national and international levels. The pharmaceutical industry in Indonesia is predicted to experience rapid growth in 2014 due to an increase in purchasing power since the start of the implementation of the Sistim Jaminan Sosial Nasional (SJSN). The purpose of this study is to determine the financial performance of  a pharmaceutical sub-sector company if it is measured by using the Return On Investment (ROI) and Residual Income (RI) through time series analysis and cross sectional approach. The sampling technique used is purposive sampling. There are 6 companies in the pharmaceutical sub-sector which are chosen as the samples in this study. The data analysis techniques used in this study are the analysis of ROI, capital cost, and RI. Financial performance of the pharmaceutical sub-sector company assessed by using time series analysis of the ROI analysis suggests that the ROI of each company is both positive and fluctuating, meanwhile assessed by using cross sectional approach of the ROI analysis suggests that there are only two companies retaining an above average rate of overall industrial ROI within three periods: PT. Merck, Tbk. and PT. Kalbe Farma, Tbk.,  Meanwhile, according to the RI analysis, both by having the time series analysis  and cross sectional approach, suggests that none of the sixth pharmaceutical sub-sector companies have an above average rate of industrial RI. Keywords : Return On Investment (ROI), Residual Income (RI), Company’s Financial Performance